IMPLEMENTATION OF SDKI AND SIKI IN COPD PATIENTS WITH NURSING PROBLEMS INEFFECTIVE AIRWAY CLEARANCE: IMPLEMENTASI SDKI DAN SIKI PADA PASIEN PPOK DENGAN MASALAH KEPERAWATAN AIRWAY CLEARANCE INEFEKTIF - Sari, Essa Novita; Wardani, Yurike Anita; Kurnianto, Syaifuddin (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2022)
Background: Ineffective airway clearance is one of the nursing problems that cause a decrease in health quality in COPD patients. Nurses need evidence-based nursing practice to enforce and overcome the nursing problem of ineffective airway clearance quickly and precisely. Purpose: This study aims to identify the signs and symptoms of major/minor ineffective airway clearance in COPD patients and identify the implementation of independent nursing actions to overcome these problems. Methods: This study uses a descriptive research design with a secondary data analysis approach that comes from the nursing care documentation of 22 respondents in 12 final project reports for the D3 Nursing Study Program FKEP UNEJ Campus Lumajang in the period 2018 to 2020. Data on major/minor signs and symptoms, as well as the implementation of independent nursing actions (based on SDKI and SIKI) identified, are presented in the distribution table for further discussion. Results: The major signs that always appeared in all respondents included: excessive sputum and additional breath sounds, and minor signs included: dyspnea and change in respiratory rate (95% of respondents). Implementation of independent nursing actions includes: giving a semi-fowler/fowler position (91% of respondents), practicing effective coughing techniques (77% of respondents), giving warm drinks (68% of respondents), doing chest physiotherapy (59% of respondents), giving oxygen therapy (36% of respondents), providing fluid intake of 2000 ml/day (18% of respondents). Conclusion: The results of this study become clinical evidence-based information that nurses can implement to increase success in caring for COPD patients with ineffective airway clearance in hospitals.